2021
DOI: 10.1111/ijcp.14415
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic phenotype was associated with better early clinical remission in elderly patients but not middle‐aged patients with acute exacerbations of COPD

Abstract: Background There is limited evidence of the relationship between peripheral blood eosinophils and clinical remission of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) at different ages, especially in elderly patients, which was the objective of the present study. Methods This retrospective study stratified patients by age (elderly patients >65 years old or middle‐aged patients between 45 and 65 years old) and analysed the relationship between blood eosinophils (≥2% or <2%) and AECOPD cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Previous studies have reported some similarities, associating eosinophilia with elevated monocytes and lymphocytes, but also observing an inverse relationship with blood neutrophils. [20][21][22] Globally, analyses of the COPDgene, ECLIPSE, SPIROMICS datasets have found variable associations between these inflammatory cells and increased blood eosinophil counts in stable COPD participants -though male predisposition is evident in most studies. [23][24][25][26] While the mechanism for the observed treatment effect is unclear, it is possible that the study participants with eosinophilia defined by a blood eosinophil count ≥300 cells/µL display a hitherto unrecognized clinical phenotype.…”
mentioning
confidence: 99%
“…Previous studies have reported some similarities, associating eosinophilia with elevated monocytes and lymphocytes, but also observing an inverse relationship with blood neutrophils. [20][21][22] Globally, analyses of the COPDgene, ECLIPSE, SPIROMICS datasets have found variable associations between these inflammatory cells and increased blood eosinophil counts in stable COPD participants -though male predisposition is evident in most studies. [23][24][25][26] While the mechanism for the observed treatment effect is unclear, it is possible that the study participants with eosinophilia defined by a blood eosinophil count ≥300 cells/µL display a hitherto unrecognized clinical phenotype.…”
mentioning
confidence: 99%